(untitled) (Eurasian Medical Research Periodical, 2023)
Chemical models of diabetes occupy the first place in experimental diabetology. Modeling of artificial skin damage in alloxan-induced diabetes, assessment of skin defect recovery, and the use of products developed on the basis of Bombyx mori fibroin for pharmacological repair of wounds, a comparative study of the regeneration process of skin wounds based on the typological response of animals